Founder CEOs and new venture media coverage - Michael D. Howard; Johannes Kolb (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2018)
Among their early key decisions, new ventures must choose whether to retain founder CEOs and how to craft a media strategy to best represent themselves to the outside world. These decisions have critical implications for firm survival and success, shaping perceptions of important external stakeholders. Our study explores the interplay between founder CEOs and media coverage and their effect on firm performance. We employ competing risk models to analyze data on 2,327 US VC-backed technology firms during the period 1985 to 2009, finding that founder CEOs enhance volume and positive tonality of media coverage, which increase the likelihood of firm IPO. Our findings provide important contributions for research into entrepreneurship and organizational reputation.
urn:nbn:de:bsz:100-opus-14558
Keywords: 330; entrepreneurship; founder characteristics; media analysis; new venture success; competing risk models